PENGARUH PROMOSI DIGITAL, STORE ATMOSPHERE DAN MOTIVASI HEDONIS TERHADAP PEMBELIAN IMPULSIF PADA WICKED VAPOR BALI - I Putu Gede Arya Gautama; I Nengah Suardhika; I Gde Yudhi Hendrawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
This study aims to examine and obtain empirical evidence about the effect of digital promotion, store atmosphere and hedonic motivation on impulse buying on Wicked Vapor Bali. The population of this research is 103 customers who have become members or subscribed. The sample of this research is the entire population. Data was collected by means of interviews, questionnaires, and documentation. Data analysis used instrument test, classical assumption test, multiple linear regression analysis, multiple correlation analysis, determination analysis and t test. The results showed that digital promotion, store atmosphere and hedonic motivation had a positive and significant effect on impulse buying on Wicked Vapor Bali. Further research can develop this research by using other variables that theoretically affect impulse buying, such as price and shopping lifestyle.